Finite Element Analysis of a Transtibial Prosthesis for a Paralympic Cyclist (2020)
(Eng) Currently, finite element analysis techniques are used to reduce costs in the manufacturing process of sports prostheses. This study primarily focuses on the finite element analysis of a design for a transtibial prosthesis for a paralympic cyclist, integra ting the biomechanics of an athlete with a double leg amputation below the knee with two prostheses categorized before the Union Cycling International (UCI) with a C - 3 disability and the characteristics of the terrain and the dynamic model. The analysis em ploying finite elements aims to evaluate the static and dynamic behavior of the proposed design when subjected to competition in the track - cycling category. As a result of this analysis, mechanical aspects, such as static forces, buckling, frequency, fatig ue, free fall, impact, and aerodynamics, can be evaluated to verify that the design of the proposed transtibial prosthesis meets an adequate aerodynamic profile and its mechanical characteristics are suitable to be used in a high - performance Paralympic cyc ling competition.